Stock Prices and Implied Abnormal Earnings Growth - AHMAD, Hafiz Imtiaz; ALPHONSE, Pascal; LEVASSEUR, Michel (International Journal of Economics and Financial Issues, 2013)
In terms of corporate valuation, the frequently used heuristics are Price Earnings or Price Earnings to Growth ratios. The development of a valuation model of type Abnormal Earnings Growth Model including modeling of expected rents evolution, conditions compatible with perfect competition, allows us to propose a testable relationship between market value of share, expected earnings per share in a year, its rate of growth in short term and a set of accounting variables composing a synthetic indicator of growth of company. Our results show that (1) expected increase in earnings per share are significantly associated with stock prices for developed countries, (2) but, the persistence of its effects is limited for emerging countries, (3) when the dynamics of growth are more complex, inclusion of synthetic variable of can make a significant correction term (4) and the implied cost of capital is significantly higher for emerging countries than for developed countries. Keywords: equity valuation; abnormal earnings; Emerging markets JEL Classifications: G12; G14; M41